GOOD TOURISM GOVERNANCE DALAM PENGEMBANGAN OBJEK WISATA PANTAI LUBUK DI DESA LUBUK KECAMATAN KUNDUR KABUPATEN KARIMUN PROVINSI KEPULAUAN RIAU TAHUN 2019-2020 - Syaiko Novrian; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Tourism is one sector that has enormous potential to be developed and now tourism development is an integral part of national development, therefore it is necessary to do very good governance in tourism development or called Good Tourism Governance. In the development of Lubuk Beach, various developments have been carried out, but the development of Lubuk beach is still not going well because there are still several criteria that have not been implemented. The purpose of this study is to find out how the implementation of Good Tourism Governance in the development of Lubuk beach and what are the inhibiting factors of the development of Lubuk Beach. This study uses the theory of Good Tourism Governance from Bambang Sunaryo, which is about the implementation of good tourism governance. The research method in this study uses a qualitative approach. The type of research used in this research is descriptive research. The research location is in Lubuk Village and several agency offices related to the development of Lubuk beach tourism objects. The types and sources of research data are divided into primary data with data collection techniques through interviews and secondary data in the form of supporting data related to the development of the Lubuk beach. The data collection techniques using interviews, documentation and observation as well as data analysis techniques in this study are qualitative descriptive. Research results from Good Tourism Governance in the Development of Lubuk Beach tourism objects in 2019-2020 have not gone well. This is because there are several criteria that have not been met in the application of Good Tourism Governance in the development of Lubuk Beach. In addition, there are also several inhibiting factors from the implementation of Good Tourism Governance in the development of Lubuk Beach, namely human resources, budget, land ownership and the Covid-19 pandemic Keywords: Good Tourism Governance, Tourism Development, Lubuk Beach, Tourism